Retention preferences and the relationship between total rewards, perceived organisational support and perceived supervisor support - Wilmien Smit; Karel Stanz; Mark Bussin (SA Journal of Human Resource Management, 2015)
Orientation: Currently there is much debate whether modifying traditional reward packages to focus on the preferences of multi-generations would be essential in attracting, motivating and retaining talent. Total reward factors, perceived organisational support and perceived supervisor support are distinct but related concepts, all of which appear to influence an employee’s decision to stay at an organisation.